Solvent-Free Enantioselective Organocatalyzed Aldol Reactions - Banon-Caballero, Abraham; Guillena, Gabriela; Najera, Carmen (Mini-Reviews in Organic Chemistry, 2014)
The use of proline as catalyst for the aldol process has given a boost to the development of organocatalysis as a research area. Since then, a plethora of organocatalysts of diverse structures have been developed for this and other organic transformations under different reaction conditions. The use of an organic molecule as catalyst to promote a reaction meets several principles of Green Chemistry. The implementation of solvent-free methodologies to carry out the aldol reaction was soon envisaged. These solvent-free processes can be performed using conventional magnetic stirring or applying ball milling techniques and are even compatible with the use of supported organocatalysts as promoters, which allows the recovery and reuse of the organocatalysts. In addition, other advantages such as the reduction of the required amount of nucleophile and the acceleration of the reaction are accomplished by using solvent-free conditions leading to a “greener” and more sustainable process.
Keywords: Aldol